Gambaran Pelaksanaan Pelayanan Farmasi Klinik Di Apotek Se-Kecamatan Gedong Tataan Kabupaten Pesawaran Lampung - Ilma Aulia; Makhdalena (STIKES Columbia Asia Medan, 2026)
Pharmaceutical services initially focusing solely on drug management (Drug Oriented) to comprehensive services that include clinical pharmacy services and medication services aimed at improving patients' quality of life (Patient Oriented). Clinical pharmacy services in pharmacies are part of pharmaceutical services that are directly responsible to patients in relation to pharmaceutical preparations, medical devices, and disposable medical supplies. This study aims to determine the implementation of clinical pharmacy services in pharmacies in the Gedong Tataan District of Pesawaran Regency. The research approach used was quantitative descriptive with a simple random sampling technique. The sample in this study consisted of 16 pharmacies and pharmacy staff working in pharmacies in the Gedong Tataan District, Pesawaran Regency, who met the inclusion and exclusion criteria. Data collection was carried out by conducting with guided interviews using questionnaires and observation on the implementation of clinical pharmacy services by pharmacy staff. The results showed that the clinical pharmacy services implemented in pharmacies in Gedong Tataan District, Pesawaran Regency, were prescription assessment and services by 74% with a good category (61-80%), dispensing by 95% with a very good category (81-100%), and drug information services (PIO) obtained a percentage of 72% with a good category (61-80%). Clinical pharmacy services were mostly carried out by Pharmacy Vocational Personnel (TVF) at 37.5%. Clinical pharmacy services in pharmacies throughout the Gedong Tataan District of Pesawaran Regency have not been fully implemented in accordance with the standards of pharmaceutical services in pharmacies according to Permenkes No. 73 of 2016, as there are still several aspects that have not been carried out.